(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background & objectives: Breast cancer is the most common cancer among females in India. Adjuvant chemotherapy regimen can cause physical and psychological distress. Chemotherapy drugs have narrow therapeutic index and cause many ADRs like neutropenia which affects the quality of life. This study assessed the effect of Granulocyte -Colony Stimulating Factors (G-CSFs) on neutropenia and quality of life in breast cancer patients.Methods: Pre-menopausal women with confirmed diagnosis of breast cancer, who have received adjuvant TAC chemotherapy regimen for 6-12 cycles were analyzed. The patients were divided in 2 groups, one group received chemotherapy only and the other received GCSF with chemotherapy. Quality of life (QOL) and incidence of febrile neutropenia (FN) in patients receiving chemotherapy were observed in each group. Assessment of QOL was done using QOL instrument of City of Hope National Medical Centre and BeckmanResearch Institute which is a questionnaire of 46-item ordinal scale that represents the four domains of quality of life including physical,psychological, social and spiritual well-being.Results: 80 patients were evaluated, out of which 40 patients received chemo + GCSF (186 cycles) and 40 patients received only chemo (172 cycles). Incidence of febrile neutropenia was seen in 4.8% and 14.5% patients receiving chemo + GCSFs and only chemo respectively. While assessing QOL, the physical domain (specifically fatigue & insomnia) was most commonly affected among other domains.Interpretations & conclusions: The use of primary GCSF was associated with reduced incidence of febrile neutropenia, anemia and other symptoms related to chemotherapy in patients having adjuvant TAC regimen.